2019
DOI: 10.5194/nhess-19-555-2019
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the eastern route of the South-to-North Water Diversion Project emergency operation on flooding and drainage in water-receiving areas: an empirical case in China

Abstract: Abstract. The water levels of lakes along the eastern route of the South-to-North Water Diversion Project (ER-SNWDP) are expected to rise significantly and subsequently affect the processes of flood control and drainage in corresponding lake basins. However, few studies have focused on the impacts of inter-basin water diversion on the flood control and drainage of water-receiving areas at the lake basin scale. Using MIKE software, this paper builds a coupled hydrodynamic model to address the existing literatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In full capacity, the SNWD project will move approximately 44.8 billion m 3 of water northward each year to meet the needs of almost half a billion people by 2050 (CAB‐SNWDP, 2003). Nonetheless, the impact of the SNWD has been one of the most hotly debated topics for a long time during the planning, design, construction, and operation phases of the project (Liu, 1998; Wang et al, 2019; Zhang et al, 2015). Previous studies of the SNWD project mainly focused on its impact on groundwater resources (Liang et al, 2019; Ye et al, 2014) and energy reductions (Zhao et al, 2017), its effect on phytoplankton (Chen et al, 2018; Zeng et al, 2015), and hydrological nitrogen and phosphorus pollution (Zhao et al, 2019), as well as the pricing system and water allocation schemes and policies (Du et al, 2019; Pohlner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In full capacity, the SNWD project will move approximately 44.8 billion m 3 of water northward each year to meet the needs of almost half a billion people by 2050 (CAB‐SNWDP, 2003). Nonetheless, the impact of the SNWD has been one of the most hotly debated topics for a long time during the planning, design, construction, and operation phases of the project (Liu, 1998; Wang et al, 2019; Zhang et al, 2015). Previous studies of the SNWD project mainly focused on its impact on groundwater resources (Liang et al, 2019; Ye et al, 2014) and energy reductions (Zhao et al, 2017), its effect on phytoplankton (Chen et al, 2018; Zeng et al, 2015), and hydrological nitrogen and phosphorus pollution (Zhao et al, 2019), as well as the pricing system and water allocation schemes and policies (Du et al, 2019; Pohlner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effectiveness of diversion canals in decreasing floodwater levels was evaluated using the HEC-RAS hydraulic model in Indonesian river basins (Indrawati et al, 2018;Nugroho et al, 2018). In addition, Wang et al (2019) examined the impacts of interbasin water diversion on flood control and drainage processes in a waterreceiving lake basin in China using the MIKE model. Subsequently, Mel et al (2020b) identified the optimal floodgate operation rules for diverting floodwater in the Bacchiglione-Brenta river network in Italy, using the 2DEF hydrodynamic model; they also evaluated the applicability of those rules (Mel et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the SWOT method has been applied in studies for solving urban ecological crises [25,26], and a model of urban ecological footprint and ecological capacity was established to analyze the ecological sustainability of regional tourism environment before putting forward the strategy of sustainable development [27]. Besides, SWOT analysis, fuzzy theory, and the ANP method [28] were used to conclude that making a consumer awareness plan is the best strategy.…”
Section: Introductionmentioning
confidence: 99%